Intraductal carcinoma of the prostate in the absence of high‐grade invasive carcinoma represents a molecularly distinct type of in situ carcinoma enriched with oncogenic driver mutations. Issue 1 (24th May 2019) - Khani, Francesca; Wobker, Sara E; Hicks, Jessica L; Robinson, Brian D; Barbieri, Christopher E; De Marzo, Angelo M; Epstein, Jonathan I; Pritchard, Colin C; Lotan, Tamara L
Abstract: Intraductal carcinoma of the prostate (IDC‐P) most often appears associated with high‐grade invasive prostate carcinoma (PCa), where it is believed to represent retrograde spread. However, IDC‐P rarely occurs as an isolated finding at radical prostatectomy or with concurrent low‐grade (Grade Group 1) invasive carcinoma. We hypothesized that isolated IDC‐P (iIDC‐P) in these unusual cases may represent a distinct in situ lesion and molecularly profiled 15 cases. iIDC‐P was characterized by copy number alteration (CNA) profiling and targeted next generation sequencing in cases with sufficient tissue ( n = 7). Immunohistochemistry for PTEN and ERG was performed on the total cohort ( n = 15), where areas of iIDC‐P and associated invasive disease were evaluated separately ( n = 9). By copy number profiling, iIDC‐P alterations were similar to those previously described in high‐grade invasive PCa ( PTEN, RB1, and CHD1 loss; MYC gain). However, in four cases, targeted sequencing revealed a striking number of activating oncogenic driver mutations in MAPK and PI3K pathway genes, which are extraordinarily rare in conventional PCa. In addition, pathogenic mutations in DNA repair genes were found in two cases of iIDC‐P ( BRCA2, CHEK2, CDK12 ) and other known PCa‐associated mutations ( FOXA1, SPOP ) in two cases. Overall, ERG was expressed in 7% (1/15) of the iIDC‐P lesions and PTEN was lost in 53% (8/15). Discordance for ERG or PTEN status between IDC‐P and the low‐grade PCa was observed in five of nine cases, with intact PTEN in the invasive tumor and PTEN loss in IDC‐P in four. Despite a CNA profile similar to conventional PCa, iIDC‐P is enriched with potentially targetable oncogenic driver mutations in MAPK/PI3K genes. Based on PTEN and ERG status, iIDC‐P is not likely a precursor to the associated low‐grade invasive PCa, but represents a molecularly unique in situ tumor of unclear clinical significance. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.